China in Global Finance Domestic Financial Repression and International Financial Power - Heep, Sandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Against the backdrop of China$1 (Bs increasingly influential role in the international financial architecture, this book seeks to characterize and evaluate China$1 (Bs financial power potential. It does so by analyzing the relationship between domestic financial repression and international financial power in the context of the political economy of the developmental state. On the basis of a novel theoretical framework for the analysis of the financial power potential of developmental states, the book provides an in-depth analysis of China$1 (Bs approach to currency internationalization, its creditor status and its policies towards the Bretton Woods institutions while contrasting the country$1 (Bs present role in global finance with the position of the Japanese developmental state in the 1980s and 1990s.s
1 Introduction -- 2 Financial Power and the Developmental State -- 3 Financial Repression and Structural Financial Power -- 4 Financial Repression and Currency Internationalization -- 5 Financial Repression and Relational Financial Power -- 6 Developmental States in the Bretton Woods Institutions -- 7 Conclusion.
Keywords: Economics; International economics; Finance; Economics/Management Science; Emerging Markets/Globalization.; Political Economy; Finance/Investment/Banking.; International Relations; Financial Economics; International Economics